Poverty Among Senior Citizens: A Canadian Success Story in International Perspective - Lars Osberg (Luxembourg Income Study (LIS), 2001)
Canada was very late in establishing a comprehensive retirement security system - lagging roughly thirty five years after the US built its Social Security system and about eighty years after Bismark first established a state funded pension system in Germany. As a consequence, the reduction in income poverty among senior citizens is a fairly recent, and very strong, trend in income distribution data in Canada. Section 1 therefore begins by describing the long run trend in poverty among senior citizens (those aged 65 and over) in Canada, and presents the 'Poverty Box' to compare the rate and depth of poverty over time, before and after taxes and transfers, among both seniors and the younger population. Section 2 discusses some of the problems of poverty measurement that are peculiar to the over 65 population. Section 3 uses Luxembourg Income Study data to compare the income changes of Canadian, American, Swedish and British households as they move into their retirement years, with particular emphasis on the income of poorer households. Section 4 concludes with some discussion of the challenges facing the design of retirement security.
Keywords: 330; Altersvorsorge; Armut; Alte Menschen; Kanada; USA; Schweden; Großbritannien